Clinical effects with customized brackets and CAD/CAM technology: a prospective controlled study - Julia Hegele; Lena Seitz; Cora Claussen; Uwe Baumert; Hisham Sabbagh; Andrea Wichelhaus (SpringerOpen, 2021)
Abstract Objective Nowadays, CAD/CAM technologies enrich orthodontics in several ways. While they are commonly used for diagnoses and treatment planning, they can also be applied to create individualized bracket systems. The purpose of this prospective quasi-randomized study was to evaluate the clinical efficiency of a customized bracket system and its comparison with directly bonded conventional self-ligating bracket treatment. Materials and methods Altogether 38 patients were separated into two groups, treated either with direct bonded self-ligating brackets (Damon, Ormco, USA) or with indirect bonded customized CAD/CAM brackets (Insignia™, Ormco, USA). Overall treatment time, number of treatment appointments, number of lost or repositioned brackets, number of arch wires and wire bends, Little Irregularity Index, cephalometric analyses and ABO scores were compared. Superimpositions of the virtual set-ups and the treatment results of the CAD/CAM group were performed to evaluate the clinical realization of the treatment planning. Results No differences between both treatment groups were found concerning overall treatment time, number of appointments and number of archwire bends. Bonding failures occurred more often using the CAD/CAM system. Indirectly bonded brackets did not have to be repositioned as often as directly bonded brackets. Treatment results with both systems were similar concerning their effects on the reduction of ABO scores. The number of used archwires was higher in the CAD/CAM group. Treatment with both systems led to further proclination of the incisors. Proclination in the lower jaw was greater than proclination in the upper jaw, and there was a statistically significant difference between the two treatment systems. Comparing the treatment results with the virtual set-ups, mesial positions were met best, followed by vertical positions. Transversal positions showed the greatest discrepancies. Concerning angles, values of angulation showed greatest accordance to the virtual set-up, while values of inclinations showed greatest discrepancies. Conclusion In comparison with a direct bonded self-ligating bracket system the use of indirect bonded customized CAD/CAM brackets showed only minor influence on treatment efficiency and treatment outcomes. Transversal expansion, deep bite correction, expression of torque and anchorage loss remain challenges in the treatment with straight-wire appliances. Trial registration DRKS, DRKS00024350. Registered 15 February 2021, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00024350 .